1995
DOI: 10.1123/jtpe.14.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Practice and Command Styles on Rate of Change in Volleyball Performance and Self-Efficacy of High-, Medium-, and Low-Skilled Learners

Abstract: This study compared volleyball achievement and task-specific self-efficacy for high-, medium-, and low-skilled learners using two teaching styles. Students were pre-, mid-, and posttested on skills and self-efficacy and were ability grouped from skill pretest scores. Learning trials were tallied for 58 students in two university classes, and growth curves for each student were created by plotting the percentages of successful trials against the 19 instructional days. ANOVA, used to determine relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
7

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
1
13
0
7
Order By: Relevance
“…In particular, post hoc analyses of the adjusted posttest means revealed no significant differences between the two teaching style groups in their effects on perceived athletic competence. This pattern of results supports those reported by other, similar studies (6,18,37). According to Graham and Heimerer (15), nonsignificant differences between instructional methodologies are not uncommon in pedagogical research.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, post hoc analyses of the adjusted posttest means revealed no significant differences between the two teaching style groups in their effects on perceived athletic competence. This pattern of results supports those reported by other, similar studies (6,18,37). According to Graham and Heimerer (15), nonsignificant differences between instructional methodologies are not uncommon in pedagogical research.…”
Section: Discussionsupporting
confidence: 91%
“…Of 18,337 references, seven studies describing eight experiments met the inclusion criteria (Table 3; Figure 1). Four were conducted in sports education (Harrison, Fellingham, Buck, & Pellett, 1995;Wulf, Lauterbach, & Toole, 1999;Wulf, McConnel, Gartner, & Schwarz, 2002), two in music education (Duke & Henninger, 1998;Henninger, Flowers, & Councill, 2006); one in critical care education (McSparron et al, 2015) and one in surgical education (Flinn et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, effective physical education teachers should recognize the potential value of both direct and indirect styles of teaching and should be trained to use a variety of them to achieve the physical education goals in the early school years (Hein & Kivimets, 2000). A general recommendation on the selection and use of teaching styles would be to focus on the learner's stage of motor development, the level of movement skill learning, and the ability of the learner to comply with the requirements of the task (Harrison, et al, 1995). In addition, given the children's need for practice opportunities and specific feedback to develop motor skills (Kraft, Smith & Buzby, 1997) and skill concepts, it is important for the teachers to recognize the performance criteria in order to provide them appropriate learning experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Harrison, Fellingham, Buck and Pellett (1995) applying the command and the practice style in college students to teach volleyball skills indicated that both were effective in terms of the percentage of successful trials. Moore (1996) studying the effect of practice and reciprocal style in improving volleyball skills of fifth grade students concluded that neither style proved to be superior to the other in helping students acquire the skills of overhand serving and forearm passing.…”
Section: Introductionmentioning
confidence: 97%